Pengembangan Model Pengukuran Wilayah Risiko Stunting Berbasis Spreadsheet di Kecamatan Harjamukti Kota Cirebon - Totok Subianto; Bambang Karmanto; Elfi Elfi (Jurnal Penelitian Kesehatan SUARA FORIKES, 2024)
Harjamukti District is an area with the highest prevalence of stunting in Cirebon City, and to overcome it, adequate, effective and efficient specific risk factor information is needed. The purpose of this study was to design a stunting risk level measurement model in the Health Center using a spreadsheet application. This study was a descriptive quantitative study using a combination of sequential exploratory models. The sample involved was 30 toddlers for each Health Center, selected using the proportionate stratified random sampling technique. In stage I, the data were analyzed descriptively, followed by the Chi-square test. In stage II, a probability risk analysis was carried out. The results of the study showed that in stage I the direct and indirect causes of stunting were identified, namely: exclusive breastfeeding, MP-ASI, LBW, BB not increasing/BGM, anemia, pregnant women with KEK, healthy homes, and clean and healthy living behaviors. In stage II, it was found that the Health Center stunting risk measurement model was categorized into 4 risk levels. Furthermore, based on the model, the risk level of each health center is known, namely: Kalitanjung Health Center = low, Kalijaga Health Center = very low, 3) Larangan Health Center = very low, Perumnas Utara Health Center = very low and Sitopeng Health Center = very high. It was concluded that the stunting risk measurement model using a spreadsheet application has succeeded in determining the stunting risk level.Keywords: stunting; measurement design; risk measurement model ABSTRAK Kecamatan Harjamukti merupakan wilayah dengan prevalensi stunting tertinggi di Kota Cirebon, dan untuk menanggulanginya diperlukan informasi faktor risiko spesifik yang adekuat, efektif dan efisien. Tujuan penelitian ini adalah merancang model pengukuran level risiko stunting di Puskesmas menggunakan aplikasi spreadsheet. Penelitian ini merupakan studi kuantitatif deskriptif menggunakan metode kombinasi model sequential exploratory. Sampel yang terlibat adalah 30 balita untuk tiap Puskemas, yang dipilih dengan teknik proportionate stratified random sampling. Pada tahap I, data dianalisis secara deskriptif, dilanjutkan dengan uji Chi-square. Pada tahap II dilakukan analisis risiko probabilitas. Hasil studi menunjukkan bahwa pada tahap I diketahui penyebab langsung dan tak langsung dari stunting yaitu: ASI eksklusif, MP-ASI, BBLR, BB tidak naik/BGM, anemia, ibu hamil dengan KEK, rumah sehat, serta perilaku hidup bersih dan sehat. Pada tahap II didapatkan bahwa model pengukuran Puskesmas risiko stunting di kategorikan menjadi 4 level risiko. Selanjutnya berdasarkan model tersebut diketahui level risiko masing-masing puskesmas yaitu: Puskesmas Kalitanjung = rendah, Puskesmas Kalijaga = sangat rendah, 3) Puskesmas Larangan = sangat rendah, Puskesmas Perumnas Utara = sangat rendah dan Puskesmas Sitopeng = sangat tinggi.  Disimpulkan bahwa model pengukuran risiko stunting menggunakan aplikasi spreadsheet berhasil menentukan level risiko stunting.Kata kunci: stunting; rancangan pengukuran; model pengukuran risiko